Ultrasound therapy in medical rehabilitation post-stroke patients - I. Samosiuk; S. Zubkova; E. Chuhraeva; N. Samosiuk; W. Zukow (Kazimierz Wielki University, 2011)
The paper presents recommendations for the use of physical exercises and massage in the treatment and rehabilitation of patients with muscular torticollis. Recommendations are intended for surgeons, doctors and exercise instructors with higher and secondary education, massage therapists and paediatricians hospitals and clinics.